A critical reflection on codes of conduct in vocational education. Issue 1 (2nd January 2018) - Bagnall, Richard G.; Nakar, Sonal
Abstract: The contemporary cultural context may be seen as presenting a moral void in vocational education, sanctioning the ascendency of instrumental epistemology and a proliferation of codes of conduct, to which workplace actions are expected to conform. Important among the purposes of such codes is that of encouraging ethical conduct, but, true to their informing instrumental epistemology, they tend to assume that ethical conduct is a formal matter: a priori, extrinsic, deductive, universal, determinate, unproblematic, incontestable, constraining and selfless. However, the context may, conversely, be seen as presenting grounds for a very different view of moral conduct as situated: immanent, intrinsic, cultural, contextualised, underdetermined, problematic, contestable, challenging and authentic. There is suggested, then, a need for vocational educators and trainers to develop the knowledge, capability, commitment and confidence to work as situated moral agents in workplaces of codified expectations to which they may be held accountable.